The Influence of Service Quality on Customer Loyalty: Expectancy-Disconfirmation Approach - Azzahra, Muthia Nathasya; Muhartini Salim (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the moderating effect of customer value on the indirect relationship between service quality and customer loyalty, with customer satisfaction acting as a mediator. Through an explanatory quantitative approach, data from 240 respondents were collected using purposive sampling and analyzed with PLS-SEM via SmartPLS. The findings align with the Expectancy Disconfirmation Theory (EDT), which says that service quality has a big impact on customer satisfaction, which in turn increases customer loyalty. Customer satisfaction is confirmed as a mediator in the relationship between service quality and loyalty. Notably, perceived value negatively moderates the service quality-satisfaction link, suggesting that higher perceived value diminishes the direct influence of service quality on satisfaction. This finding offers a nuanced perspective within the EDT framework. The study contributes theoretically and practically by highlighting the importance of understanding moderating factors in customer behavior. Future research should explore additional variables influencing this relationship.